Peran Notaris terhadap Kepastian Hukum dalam Kepemilikan Satuan Rumah Susun oleh Warga Negara Asing - Hanifiah, Annisa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
A flat unit (sarusun) is a multi-storey building built in an environment with parts arranged functionally both horizontally and vertically. Each unit in this building can be owned and used separately, especially as a residence, and is equipped with parts, objects and land that are owned together. Foreign citizens (WNA) in Indonesia can own an apartment unit with the status of Right to Use State Land, as proven by an Apartment Unit Certificate. Ownership of a flat can be done through buying and selling, renting or inheriting. The buying and selling process is carried out before a notary, and the notary plays an important role in ensuring that the property rights given to foreigners are in accordance with applicable regulations. Ownership of flats by foreigners is only permitted in Special Economic Zones (KEK).